The Territorial Disparities Of Development: Synthetic Hdi By Delegation In Tunisia - Bousnina, Adel (جامعة الوادي - University of Eloued, 2023)
The aim of this article is to analyze the territorial and local disparities of development in Tunisia. The interest will be focused on composite indicators of human development by region and especially by delegation and the HDI (human development index) or synthetic indicator of human development in all the delegations of Tunisia. Finally, in each governorate, we will analyze the main factors and the different causes and explanations of local inequalities.
مقال
Keywords: Territorial disparities ; delegations ; HDI ; Human development